Impact Assessments in Finance and Private Sector Development : What Have We Learned and What Should We Learn? - McKenzie, David (World Bank, 2012)
Until recently rigorous impact evaluations have been rare in the area of finance and private sector development. One reason for this is the perception that many policies and projects in this area lend themselves less to formal evaluations. However, a vanguard of new impact evaluations on areas as diverse as fostering microenterprise growth, microfinance, rainfall insurance, and regulatory reform demonstrates that in many circumstances serious evaluation is possible. The purpose of this paper is to synthesize and distill the policy and implementation lessons emerging from these studies, use them to demonstrate the feasibility of impact evaluations in a broader array of topics, and thereby help prompt new impact evaluations for projects going forward.